The geometry of the compound leaf plays a significant role in the leaf movement of Medicago truncatula modulated by mtdwarf4a. Issue 2 (16th February 2021) - Zhao, Weiyue; Bai, Quanzi; Zhao, Baolin; Wu, Qing; Wang, Chaoqun; Liu, Ye; Yang, Tianquan; Liu, Yu; He, Hua; Du, Shanshan; Tadege, Million; He, Liangliang; et al.
Summary: In most legumes, two typical features found in leaves are diverse compound forms and the pulvinus‐driven nyctinastic movement. Many genes have been identified for leaf‐shape determination, but the underlying nature of leaf movement as well as its association with the compound form remains largely unknown. Using forward‐genetic screening and whole‐genome resequencing, we found that two allelic mutants of Medicago truncatula with unclosed leaflets at night were impaired in MtDWARF4A ( MtDWF4A ), a gene encoding a cytochrome P450 protein orthologous to Arabidopsis DWARF4. The mtdwf4a mutant also had a mild brassinosteroid (BR)‐deficient phenotype bearing pulvini without significant deficiency in organ identity. Both mtdwf4a and dwf4 could be fully rescued by MtDWF4A, and mtdwf4a could close their leaflets at night after the application of exogenous 24‐epi‐BL. Surgical experiments and genetic analysis of double mutants revealed that the failure to exhibit leaf movement in mtdwf4a is a consequence of the physical obstruction of the overlapping leaflet laminae, suggesting a proper geometry of leaflets is important for their movement in M. truncatula . These observations provide a novel insight into the nyctinastic movement of compound leaves, shedding light on the importance of open space for organ movements in plants.